2022
DOI: 10.3390/su142315870
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Life Cycle Assessment in Organic and Conventional Rice Farming Systems: Using a Cradle to Farm Gate Approach

Abstract: The rising demand for agricultural products and expanding public awareness of environmental friendliness have led to the adoption of the organic farming system rather than the conventional one. The life cycle assessment (LCA) concept is a frequently used method to examine the environmental impacts of any activity across its entire life cycle. This research is the first use of LCA for the impacts of vermicompost and cattle manure as organic fertilizers in rice farming. The main goal of this study was to compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 91 publications
0
16
0
1
Order By: Relevance
“…The results showed that compost application reduced FETP by 19.1% in dryland and 36.2% in irrigated farming. The toxicity impact is mostly caused by the emission of nitrogen dioxide (NO 2 ) into the air or soil [ 67 ], which is significantly reduced by compost application in both dryland and irrigated farming ( Table 2 and Table 3 ). Soil toxicity is related to the use of fertilizers and chemical pesticides in agriculture, and soil is a significant pollution sink due to particle adsorption on the soil surface [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that compost application reduced FETP by 19.1% in dryland and 36.2% in irrigated farming. The toxicity impact is mostly caused by the emission of nitrogen dioxide (NO 2 ) into the air or soil [ 67 ], which is significantly reduced by compost application in both dryland and irrigated farming ( Table 2 and Table 3 ). Soil toxicity is related to the use of fertilizers and chemical pesticides in agriculture, and soil is a significant pollution sink due to particle adsorption on the soil surface [ 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…In recent years, organic amendments such as manure, compost, and straw have been used to improve the environment for rice production [11]. Among them, straw incorporation is recognized as an effective method to maintain or improve rice yield and soil quality [12].…”
Section: Introductionmentioning
confidence: 99%
“…While fertilization plays an important role in ensuring food security, over-fertilization will reduce crop yields, accelerate soil acidification, increase greenhouse gas emissions, and ultimately reduce economic income [17][18][19][20]. Organic farming has less negative impact on the environment than conventional farming based on chemical fertilizers [21].The long use of mineral fertilizers has caused irreparable damage to soil structures, mineral cycles, soil microbial flora, and plants [22][23][24]. Intensified N fertilization decreased the content of dry matter and starch in potato tubers [25,26].…”
Section: Introductionmentioning
confidence: 99%